2022
DOI: 10.21203/rs.3.rs-1445747/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The preference signature of the SARS-CoV-2 Nucleocapsid NTD for its 5’-genomic RNA elements

Abstract: The nucleocapsid protein (N) of SARS-CoV-2 plays a pivotal role during the viral life cycle. It is involved in RNA transcription and accounts for packaging of the large genome into virus particles. N manages the enigmatic balance of bulk RNA-coating versus precise RNA-binding to designated cis-regulatory elements. Numerous studies report the involvement of its disordered segments in non-selective RNA-recognition, but how N organizes the inevitable recognition of specific motifs remains unanswered. We here use … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…On the other hand, several regions show higher flexibility (red, low R 2 / R 1 ratios). These comprise the finger (residues 92-106), a few external loops, and the residues at the edges of the construct, as also previously reported in the literature [ 24 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…On the other hand, several regions show higher flexibility (red, low R 2 / R 1 ratios). These comprise the finger (residues 92-106), a few external loops, and the residues at the edges of the construct, as also previously reported in the literature [ 24 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 62%
“…It is interesting to compare our results with recent studies focusing on the interaction of NTD with different fragments of nucleic acids. Indeed, NMR spectra were used to follow CSPs of NTD upon the addition of increasing concentrations of nucleic acid fragments to map interaction surfaces [ 19 , 22 , 25 , 58 , 72 ]. The region of the basic finger is generally extensively perturbed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether sequence specificity can affect affinity and mode of binding of the specific RNA with the disordered region, we studied the interactions with a 21 nucleotide sequence (V21) from the 5’ UTR of the viral genome. This region of the genome was previously found interacting with the N protein in in cell crosslinking studies [10] and has been confirmed to adopt no secondary structure at room temperature [39] .…”
Section: Resultsmentioning
confidence: 95%
“…The N-terminal RBD (NTD) interacts with RNA as a monomer and its interactions with ss and double-stranded (ds) RNA have been modelled 7 . Recent studies support the idea that despite being a promiscuous RNA binder, NTD binds to a variety of RNA structures with different signatures, suggesting a possible mechanism for regulation and RNA processing 8,9 . On the other hand, the C-terminal RBD (CTD) is present in solution as a swapped dimer as determined by x-ray crystallography, however little is known about the structural details of RNA recognition 10,11 .…”
Section: Introductionmentioning
confidence: 80%